Assessment of Sleep-Related Problems in Children with Cerebral Palsy Using the SNAKE Sleep Questionnaire - Larissa Alice Dreier; Tugba Kapanci; Katharina Lonnemann; Margarete Koch-Hogrebe; Lucia Wiethoff-Ubrig; Markus Rauchenzauner; Markus Blankenburg; Boris Zernikow; Julia Wager; Kevin Rostasy (MDPI AG, 2021)
Cerebral palsy (CP) represents the most common motor impairment in childhood. The presence of sleep problems has not yet been investigated with an instrument specifically designed for this population. In this hospital-based, prospective study, N = 100 children (M = 7.9, range: 2-18 years) with CP were included. All patients underwent pediatric neurologists' screening incorporating instruments (Data Collection Form; Gross Motor Functions Classification System, GMFCS; Bimanual Fine Motor Function, BFMF) recommended by the "Surveillance of Cerebral Palsy in Europe (SCPE)". Parents completed the "Sleep Questionnaire for Children with Severe Psychomotor Impairment (SNAKE)". Children's sleep behavior was increasingly conspicuous, with greater gross motor (SNAKE scales: disturbances remaining asleep, daytime sleepiness) and fine motor (additionally SNAKE scale arousal and breathing problems) functional impairment. Overall, a proportion of children showed sleep behavior outside the SNAKE's normal range. No relevant sleep differences were identified between different CP subtypes and comorbidities. Applying a population-specific questionnaire, children's functional impairment seems to be more relevant to their sleep behavior than the CP subtype or CP comorbidities.